Involvement of oxidative species in cyclosporine-mediated cholestasis - Nsengimana, Bernard; Okpara, Edozie Samuel; Hou, Wanqing; Yan, Chuyun; Han, Shuxin (Frontiers in Pharmacology, 2022)
Cyclosporine is an established medication for the prevention of transplant rejection. However, adverse consequences such as nephrotoxicity, hepatotoxicity, and cholestasis have been associated with prolonged usage. In cyclosporine-induced obstructive and chronic cholestasis, for example, the overproduction of oxidative stress is significantly increased. Additionally, cyclosporine exerts adverse effects on liver function and redox balance responses in treated rats, as evidenced by its increasing levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and bilirubin while also decreasing the levels of glutathione and NADPH. Cyclosporine binds to cyclophilin to produce its therapeutic effects, and the resulting complex inhibits calcineurin, causing calcium to accumulate in the mitochondria. Accumulating calcium with concomitant mitochondrial abnormalities induces oxidative stress, perturbation in ATP balance, and failure of calcium pumps. Also, cyclosporine-induced phagocyte oxidative stress generation via the interaction of phagocytes with Toll-like receptor-4 has been studied. The adverse effect of cyclosporine may be amplified by the release of mitochondrial DNA, mediated by oxidative stress-induced mitochondrial damage. Given the uncertainty surrounding the mechanism of cyclosporine-induced oxidative stress in cholestasis, we aim to illuminate the involvement of oxidative stress in cyclosporine-mediated cholestasis and also explore possible strategic interventions that may be applied in the future.